2016
DOI: 10.1002/acr.22835
|View full text |Cite
|
Sign up to set email alerts
|

Axl, Ferritin, Insulin‐Like Growth Factor Binding Protein 2, and Tumor Necrosis Factor Receptor Type II as Biomarkers in Systemic Lupus Erythematosus

Abstract: Objective-To evaluate the performance of 4 serum protein markers for detecting concurrent clinical activity in patients with systemic lupus erythematosus (SLE).Methods-Consecutive patients who fulfilled ≥4 ACR criteria for SLE and healthy controls were recruited for serological testing of 4 protein markers identified by antibody-coated microarray screen, namely Axl, ferritin, IGFBP2 and TNFR2. SLE disease activity was assessed by the SELENA-SLEDAI and physician's global assessment (PGA). Levels of these marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 36 publications
(39 reference statements)
2
23
0
Order By: Relevance
“…Most of these cells express Mer and Axl but little or no Tyro3 . Our result indicated that sMer, sAxl and GAS6 levels were higher in SLE patients with LN, which agrees with previous studies . In the ROC analysis of TAM receptors and ligands to identify patients with lupus nephritis, area under the curve (AUC) of MER (0.732), sAXL (0.7148) and Gas6(0.7357) were significantly higher than that of sTYRO3 (0.5443) and protein S (0.5773).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Most of these cells express Mer and Axl but little or no Tyro3 . Our result indicated that sMer, sAxl and GAS6 levels were higher in SLE patients with LN, which agrees with previous studies . In the ROC analysis of TAM receptors and ligands to identify patients with lupus nephritis, area under the curve (AUC) of MER (0.732), sAXL (0.7148) and Gas6(0.7357) were significantly higher than that of sTYRO3 (0.5443) and protein S (0.5773).…”
Section: Discussionsupporting
confidence: 90%
“…35 Our result indicated that sMer, sAxl and GAS6 levels were higher in SLE patients with LN, which agrees with previous studies. 14,16,27,[36][37][38] In the ROC analysis of TAM receptors and ligands to identify patients with lupus nephritis, area under the curve (AUC) of MER (0.732), sAXL (0.7148) and Gas6(0.7357) were significantly higher than that of sTYRO3 (0.5443) and protein S (0.5773). Therefore, it was suggested that sMer, sAXL and GAS6 may be a useful addition to the panel of biomarkers of LN.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the soluble form may lead to the inactivation of the TAM receptors with reducing membrane‐bound receptors and neutralization of the TAM ligands as a decoy receptor . Recently, the different roles of soluble TAM receptors have been implicated in the autoimmune disease, which may even act as a potential biomarker . Both the other studies and our previous study revealed that the sMer and sAxl levels in plasma were correlated positively with disease activity and nephritis in systemic lupus erythematosus (SLE) patients .…”
Section: Introductionmentioning
confidence: 87%
“…Thus, new biomarkers to identify early renal involvement in SLE patients are being soug ht [24][25][26][27][28][29][30][31]. An ideal biomarker should detect disease activity and renal involvement and damage as early as possible to enable prompt treatment and minimise organ damage [32].…”
Section: Discussionmentioning
confidence: 99%